Simulation Study of Propylene Glycol Formation from Propylene Oxide and Water: Effect of Reactor Type, Reactant Ratio, Temperature, and Reactor Configuration - Eko Ariyanto; Eka Sri Yusmartini; Robiah Robiah; Feby Ardianto (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
This study investigates the influence of reactor type, reactor configuration, reactor temperature, and reactant ratio on the formation of propylene glycol from propylene oxide and water using HYSYS simulation software. The examined reactor types include Continuous Stirred Tank Reactors (CSTR) and Plug Flow Reactors (PFR). The impact of reactant ratio is explored by varying the mole ratio of propylene oxide to water. The effect of temperature is studied by altering the reaction temperature from 24 to 40 Â°C. HYSYS simulation results reveal that PFR yields the highest conversion compared to CSTR. Furthermore, consecutive CSTR configuration produces higher conversion than parallel CSTR configuration. Additionally, an increase in reaction temperature from 24 to 40 Â°C enhances the conversion of propylene oxide to propylene glycol. The reactant ratio 1:1 (propylene oxide to water) yields the highest conversion compared to other reactant ratios. The implications of these findings are to provide insights into more efficient and economical propylene glycol processes. The study suggests that PFR configuration, consecutive CSTR configuration, elevated reactor temperatures, and optimal reactant ratios can significantly improve the efficiency of propylene glycol formation.Keywords: Propylene Glycol, CSTR, PFR, Conversion, HYSYS Simulation